A rare variant case of pure esophageal atresia with an atretic segment - Kazunori Masahata; Toshimichi Hasegawa; Seika Kuroda; Nobumasa Takahashi; Ikuko Nojima; Noriko Kimura; Keiji Tsuchimoto; Akio Kubota (Elsevier, 2015)
Pure esophageal atresia is typically characterized by a long gap between the upper and lower pouches, with a gasless abdomen and no fistula. The association of pure esophageal atresia with an atretic segment is extremely rare. We report a rare variant case of pure esophageal atresia in which the two blind esophageal pouches were joined by an atretic segment. Excision of the atretic segment and primary anastomosis were performed successfully.